ChargeMate: EV Charging Station Finder and Booking Platform - Jaiswal, Harsh; Patel, Gaurank; Kumar, Shubham; Singh, Sarika (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The rise of Electric Vehicles (EV) for transportation has created a huge demand for a vast and technically robust charging infrastructure to enhance the adoption and integration of electric vehicles. However, limited visibility and access to charging stations have emerged as major obstacles to the widespread adoption of electric vehicles. ChargeMate is a web-based platform designed to bridge this gap by enabling users to locate, view, and reserve EV charging slots in real time. Developed using Python (Flask) and MySQL, ChargeMate offers a user-friendly interface, real-time data updates, and a robust admin management panel for station operators. This paper discusses existing solutions, highlights gaps in the current EV charging ecosystem, proposes a scalable and discusses the outcomes achieved through the developed platform.
Keywords: Electric Vehicles; Charging Stations; Slot Booking; Real-Time Reservation; Sustainable Transportation; Web Platform; Python Flask; EV Infrastructure